A study of stylistic devices in "Girl with a pearl earring" by Tracy Chevalier - Lê, Phan Lệ Thu. (2014)
This study is carried out with the aim of giving a living proof of the natural bridge between stylistic devices and literature. Through a careful investigation into metaphor and simile – the two typical stylistic devices which are used concentratedly and distinctively in the novel “Girl with a Pearl Earring” by Tracy Chevalier, and other stylistic devices such as metonymy, alliteration, repetition, etc., the author truly hopes to prove the important role of stylistics and stylistic devices to literary analysis. Both qualitative and quantitative methods were used and illustrated to make the study a profound and widespread descriptive analysis. Based on approximately 400 collected samples used in the novel, the expressive means embodying metaphor and simile were classified into different tables according to their part of speech, their structure and their semantic features. In general, simile is used at the highest frequency, then comes metaphor. Some other stylistic devices such as repetition, symbol and alliteration, etc. have smaller number. Finally, based on the findings and results of this study, some implications for the teaching and learning English literature will also be suggested.